2009
DOI: 10.1016/j.bmcl.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Aryl diketoacids (ADK) selectively inhibit duplex DNA-unwinding activity of SARS coronavirus NTPase/helicase

Abstract: As anti-HCV aryl diketoacids (ADK) are good metal chelators, we anticipated that ADKs might serve as potential inhibitors of SARS CoV (SCV) NTPase/helicase (Hel) by mimicking the binding modes of the bismuth complexes which effectively competes for the Zn(2+) ion binding sites in SCV Hel thereby disrupting and inhibiting both the NTPase and helicase activities. Phosphate release assay and FRET-based assay of the ADK analogues showed that the ADKs selectively inhibit the duplex DNA-unwinding activity without si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…Analysis of amino acid sequence suggests that the SCV helicase has 2 separate domains: (1) a metal-binding domain (MBD) at the N-terminus and (2) a helicase domain (Hel) [22]. A detailed understanding of the biochemical mechanism mediated by SCV helicase became possible [25][26][27][28][29] after its purification [6,30].…”
Section: Characterization Of the Scv Helicase Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of amino acid sequence suggests that the SCV helicase has 2 separate domains: (1) a metal-binding domain (MBD) at the N-terminus and (2) a helicase domain (Hel) [22]. A detailed understanding of the biochemical mechanism mediated by SCV helicase became possible [25][26][27][28][29] after its purification [6,30].…”
Section: Characterization Of the Scv Helicase Proteinmentioning
confidence: 99%
“…Further, Lee et al recently identified some aryl diketoacids (ADKs) as chemical inhibitors of SCV helicase. However, in contrast to myricetin and scutellarein, they appeared to inhibit the duplex DNA-unwinding activity but not the ATPase activity of SCV helicase [26]. They have expanded the study by showing that dihydroxychromone derivatives, which are structural analogs of ADKs, can function as chemical inhibitors of the DNA-unwinding activity, but not of the ATPase activity, of SCV helicase [27].…”
Section: Development Of Chemical Inhibitors Of the Scv Helicase Nsp13mentioning
confidence: 99%
“…Since the viral helicase has been identified as a potential target for therapy in other viruses due to its indispensability in viral genome replication (10)(11)(12), SCV NTPase/ Helicase (nsP13), which was recently purified and characterized, was suggested as an attractive target for the development of anti-SCV agents (7). Thus, a lot of efforts have been made to identify and test small molecule inhibitors of the SCV helicase as drug candidates (13)(14)(15)(16). RNA and DNA aptamers against SCV helicase were also reported to have an inhibitory effect against nucleic acids unwinding (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Several viral helicases have been used as proven drug targets due to the inhibition of helicase activity in animal models of herpes simplex virus (HSV) and in the treatment of hepatitis C 14,15 . Therefore, much effort has been spent on the development of small-molecule inhibitors and chemicals as drug candidates to inhibit the function of SARS coronavirus helicase nsP13 (SCV nsP13) [16][17][18][19][20] . Helicases are motor proteins that unwind a double-stranded (ds) nucleic acid into two single-stranded (ss) nucleic acids using energy derived from NTP hydrolysis during translocation along a single strand for nucleic acid replication, recombination, and DNA repair [21][22][23][24] .…”
mentioning
confidence: 99%